Efeito da temperatura na germina̧ão de sementes de Sebastiania commersoniana (Baillon) Smith & Downs separadas pela colora̧ão do tegumento - Santos, Sérgio Roberto Garcia dos; Aguiar, Ivor Bergemann de [UNESP] (My University, 2005)
Sebastiania commersoniana (Euphorbiaceae) is a tree species of riparian forests in Brazil. Seeds of this species released from mature fruits have heteromorphy in coat colour: dark (dark-brown to black), striated (dark with light-grey stria) and clear (light-grey to whitish). In this work two experiments were carried out in order to study the effect of temperature on seed germination in interaction with coat colour. Germination final percentage and speed index were evaluated. In the first experiment seeds of the three colours were submitted to constant (30°C) and alternating (20-35°C) temperatures. For all the seed colours, best results were obtained at alternating temperature. Physiological quality of striated seeds was greater than those clear seeds and dark seeds were intermediate. In the second experiment striated and clear seeds were submitted to three amplitudes of alternating temperature: 5°C (20-25°C and 25-30°C), 10°C (20-30°C and 25-35°C) and 15°C (20-35°C). Both germination percentage and speed were higher in striated seeds and for the two seed colours, best results were obtained at 20-30°C and 20-35°C. These temperatures are recommended for the germination test.
Effect of temperature on Sebastiania commersoniana (Baillon) Smith & Downs seed germination separated by coat colour
Keywords: Coat colour; Forest seed; Germination; Physiological quality; Sebastiania commersoniana; Temperature; Coat color; Biodiversity; Forestry; Seed; Forests; Seeds